Differences in Social Emotional Skills Early Childhood who Attend School from 3 Years Old and 5 Years Old (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
Early childhood education is very important in shaping children's development, especially their social and emotional abilities. The purpose of this study was to compare the significant social emotional development between two pre-school age groups in Kupang city, NTT, namely children who started PAUD at the age of 3 years and children who started PAUD when they were 5 years old. This study used comparative quantitative methodology, the survey method, and analytical methodology. Data collection techniques were obtained through the survey method using a validated social-emotional ability instrument consisting of 47 indicator items filled in by respondents (especially mothers) and child data obtained from schools. The sample was 57 kindergarten B children who attended school from the age of 3 years and 59 children who attended school at the age of 5 years. The total number of respondents was 116 children from 5 kindergartens in the Coconut Lima sub-district of Kupang City, NTT. The sample was selected using random sampling technique. Data collection was conducted in July–August 2024. The results showed that kindergarten B children who attended PAUD since the age of 3 years and who started school at the age of 5 years had significant differences in social and emotional abilities. Based on the “significance value above 0.001 <0.05” using the mean score of 3-year-olds (119.17) and 5-year-olds (75.1), it can be concluded that 3-year-olds are more emotionally capable than 5-year-olds